2010
DOI: 10.1063/1.3483136
|View full text |Cite
|
Sign up to set email alerts
|

Magnonic spin-wave modes in CoFeB antidot lattices

Abstract: In this manuscript time-resolved magneto-optical Kerr effect experiments on structured CoFeB films are presented. The geometries considered are two dimensional square lattices of micrometer-sized antidots, fabricated by a focused ion beam. The spin-wave spectra of these magnonic crystals show a novel precessional mode, which can be related to a Bloch state at the zone boundary. Additionally, another magnetic mode of different nature appears, whose frequency displays no dependence on the externally applied magn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
54
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 23 publications
2
54
0
1
Order By: Relevance
“…4 Ferromagnetic resonance measurements evidenced a small linewidth for CoFeB. [5][6][7][8][9][10] For magnonic applications, 11,12 electrically generated spin waves would be very interesting.…”
mentioning
confidence: 99%
“…4 Ferromagnetic resonance measurements evidenced a small linewidth for CoFeB. [5][6][7][8][9][10] For magnonic applications, 11,12 electrically generated spin waves would be very interesting.…”
mentioning
confidence: 99%
“…More detailed pulsed-field experiments have revealed that, in micro-scale and sub-micron sized samples, the coherence of spin precession somewhat deteriorates because of shape anisotropy effects, leading to the appearance of multi-mode spin-wave excitations. [18][19][20][21][22][23][24] Nevertheless, even in this case, the coherent suppression of ringing has been demonstrated. 25 From a different point of view, spin ringing with a large lifetime in a material with high magnetic Q-factor like yttrium iron garnet (YIG) can be more of a benefit than a problem.…”
mentioning
confidence: 85%
“…[16] Over the last decade several works have been reported on the control of SW dynamics in MAL arrays by varying the antidot architecture. [18][19][20][21][22][23][24] Further the most desired characteristics of a material for magnonic based applications are low magnetic damping, high saturation magnetization, high curie temperature, long spin wave propagation distance, etc. [1] Among various materials reported till date, Yttrium Iron garnet (YIG) possesses remarkably low magnetic damping of ∼0.0002 and high SW propagation distance of ∼22.5 µm.…”
Section: Introductionmentioning
confidence: 99%